Galaxy And Mass Assembly (GAMA): testing galaxy formation models through the most massive galaxies in the Universe. Issue 1 (8th March 2014) - Oliva-Altamirano, P.; Brough, S.; Lidman, C.; Couch, W. J.; Hopkins, A. M.; Colless, M.; Taylor, E.; Robotham, A. S. G.; Gunawardhana, M. L. P.; Ponman, T.; Baldry, I.; Bauer, A. E.; et al.
Abstract: We have analysed the growth of Brightest Group Galaxies and Brightest Cluster Galaxies (BGGs/BCGs) over the last 3 billion years using a large sample of 883 galaxies from the Galaxy And Mass Assembly survey. By comparing the stellar mass of BGGs and BCGs in groups and clusters of similar dynamical masses, we find no significant growth between redshift z = 0.27 and 0.09. We also examine the number of BGGs/BCGs that have line emission, finding that approximately 65 per cent of BGGs/BCGs show Hα in emission. From the galaxies where the necessary spectroscopic lines were accurately recovered (54 per cent of the sample), we find that half of this (i.e. 27 per cent of the sample) harbour ongoing star formation with rates up to 10 M⊙ yr −1, and the other half (i.e. 27 per cent of the sample) have an active nucleus (AGN) at the centre. BGGs are more likely to have ongoing star formation, while BCGs show a higher fraction of AGN activity. By examining the position of the BGGs/BCGs with respect to their host dark matter halo, we find that around 13 per cent of them do not lie at the centre of the dark matter halo. This could be an indicator of recent cluster–cluster mergers. We conclude that BGGs and BCGs acquired their stellar mass rapidly at higher redshifts as predicted by semi-analytic models, mildly slowing down at low redshifts.